Professionals and interfamily violence against children and adolescents: in between legal and conceptual precepts - Gabriele Schek; Mara Regina Santos da Silva; Carl Lacharité; Maria Emilia Nunes Bueno
Abstract OBJECTIVE To identify the conceptions of professionals regarding interfamily violence against children and adolescents. METHOD A qualitative study conducted with 15 professionals who had taken children and adolescents under their care as a result of interfamily violence. Data were collected between November, 2013, and March, 2015, through semi-structured interviews. Data were organized and analyzed using the Textual Discourse Analysis technique. RESULTS The professional discourse highlighted that some legal aspects regarding the handling of interfamily violence against children and adolescents are neglected; an omission supported by the justification of professionals to preserve the family. We highlight the confrontation between the concept of family as a caregiver and the family that commits violence against children, in addition to the positioning of professionals, which does not include the family or the aggressor in the intervention process in facing situations of interfamily violence attended to by the services. CONCLUSION Acting against interfamily violence requires professionals to do away with some pre-established concepts in ordee to put the actual needs of victims and families into evidence.